Differences in functioning between young adults with cancer and older age groups: A cross‐sectional study. (17th July 2022) - Andersen, Nanna Hejselbaek; Christiansen, Josephine Aagesen; la Cour, Karen; Aagesen, Maria; Tang, Lars Hermann; Joergensen, Dorthe Soested; Pilegaard, Marc Sampedro
Abstract: Objective: This study aimed to explore whether young adults with cancer have different functioning compared to older age groups with cancer. Methods: This study is a cross‐sectional study including 654 adults (≥18 years) with cancer. Exposure was age groups categorised as (1) young adults ( n = 121) = 18–39 years; (2) middle‐aged adults ( n = 406) = 40–64 years; and (3) older people ( n = 127) = ≥65 years. Outcomes were physical, role, social and cognitive functioning. Analyses consisted of linear regression models. Results: Middle‐aged adults had a statistically significant worse physical functioning compared to young adults (−3.90: [95% CI: −6.84; −0.95]). The older age group also had a statistically significant worse physical functioning compared to young adults (−7.63: [95% CI: −11.29; −3.96]). Young adults had statistically significant lower role functioning (−7.11: [95% CI: −1.13; −13.08]) and cognitive functioning (−13.82: [95% CI: −7.35; −20.29]) compared to the older age group. There was no statistically significant difference in social functioning between the age groups. Conclusion: Young adults with cancer seem to have other functioning problems compared with higher age groups. These findings support current research regarding the need to develop age‐specific and appropriate rehabilitation services for young adults with cancer.